2020
DOI: 10.3390/molecules25061448
|View full text |Cite
|
Sign up to set email alerts
|

Removal of V(V) From Solution Using a Silica-Supported Primary Amine Resin: Batch Studies, Experimental Analysis, and Mathematical Modeling

Abstract: Every year, a large quantity of vanadium-containing wastewater is discharged from industrial factories, resulting in severe environmental problems. In particular, V(V) is recognized as a potentially hazardous contaminant due to its high mobility and toxicity, and it has received considerable attention. In this study, a silica-supported primary amine resin (SiPAR) was prepared by in-situ polymerization, and the V(V) adsorption from the solution was examined. The as-prepared resin exhibited fast adsorption kinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…A study in China identified vanadium in soils and groundwater where species from the Bacillus and Thauera genera were well represented, resulting in reduction of V 5+ to less toxic V 4+ suggesting a path to bioremediation with these species ( Zhang et al, 2019 ). Vanadium can also be recovered by chemical and biological sorbents for both remediation and industrial vanadium recovery ( Huang et al, 2020 ; Kong et al, 2020 ; Zhang and Leiviskä, 2020 ; Sharififard and Rezvanpanah, 2021 ). However, the paucity of microbiological studies highlights the gap in current knowledge of vanadium-contaminated environments.…”
Section: Introductionmentioning
confidence: 99%
“…A study in China identified vanadium in soils and groundwater where species from the Bacillus and Thauera genera were well represented, resulting in reduction of V 5+ to less toxic V 4+ suggesting a path to bioremediation with these species ( Zhang et al, 2019 ). Vanadium can also be recovered by chemical and biological sorbents for both remediation and industrial vanadium recovery ( Huang et al, 2020 ; Kong et al, 2020 ; Zhang and Leiviskä, 2020 ; Sharififard and Rezvanpanah, 2021 ). However, the paucity of microbiological studies highlights the gap in current knowledge of vanadium-contaminated environments.…”
Section: Introductionmentioning
confidence: 99%